International law - Klabbers, Jan (Cambridge, 2017)
"Written by one of the world's leading international lawyers, this is the new and updated edition of Jan Klabber's landmark textbook. International law can be defined as 'the rules governing the legal relationship between nations and states', but in reality it is much more complex, with political, diplomatic and socio-economic factors shaping the law and its application. This refreshingly clear, concise textbook encourages students to view international law as a dynamic system of organizing the world. Bringing international law back to its first principles, the book is organised around four questions: where does it come from? To whom does it apply? How does it resolve conflict? And what does it say? Building on these questions with both academic rigour and clarity of expression, Professor Klabbers breathes life and energy into the subject. Footnotes point students to the wider academic debate while chapter introductions and final remarks reinforce learning. The second edition has been updated throughout, with particular attention to recent judicial decisions, and features new sections on sovereign debt relief, the prompt release of vessels, and the Antarctic"--